Impact face influence on low velocity impact performance of interply laminated plates - Manikandan, Periyasamy (2018)
Fibre Metal Laminate (FML), a metal sandwiched hybrid composite material is well-known for its enhanced impact properties and better damage tolerance and it has been successfully implemented in diverse engineering applications in aviation industry. With heterogeneous constituents, the stacking sequence of FML is believe to play a critical role to govern its overall energy absorption capability by means of controlling delamination of metal composite interface and plastic deformation of metal layers. As a precursor, low velocity impact experiments were conducted on interply configured transparent plastic plates in order to extract the significance of stacking sequence and realize the characteristics of each layer through naked eye which is not possible in FML due to opacity of metal layer. The stack configuration constitute hard acrylic (brittle) and soft polycarbonate (ductile) plates analogous to composite (brittle) and metal (ductile) layers on FML laminate and the impact event is performed on either hard or soft facing sides separately. Hard side samples resemble more protective than soft side impact sample, with large peak resistant force and expose smaller damage growth in all experimented cases.